Regularity for Elliptic Equations under Minimal Assumptions - Giuseppe Di Fazio (Journal of the Indonesian Mathematical Society, 2020)
The aim of this paper is to give a brief account on the problem of regularity forlinear elliptic PDEs of the second order.